2003
DOI: 10.1108/09513570310472058
|View full text |Cite
|
Sign up to set email alerts
|

The development of the specialist accounting history literature in the English language

Abstract: This study focuses on the participation of women in the development of the specialist international accounting history literature. Specifically, based on data collected from the three specialist, internationally refereed, accounting history journals in the English language from the time of first publication in each case, the study provides evidence of the involvement of women through publication, through membership of editorial boards and editorial advisory boards and also through holding editor, associate edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 35 publications
(69 reference statements)
1
49
0
2
Order By: Relevance
“…Important developments in the accounting history area result an increase in the publications in this area (Carnegie et al 2003;Carmona, 2006, De Serra Faria, 2008Sánchez-Matamoros & Hidalgo, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Important developments in the accounting history area result an increase in the publications in this area (Carnegie et al 2003;Carmona, 2006, De Serra Faria, 2008Sánchez-Matamoros & Hidalgo, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years there are several researches conducted studies on the publishing patterns of the academicians in accounting history (Carnegie & Napier, 2002;Anderson, 2002;Carnegie et al, 2003;Williams & Wines, 2006;Shimizu et al, 2007;De Serra Faria, 2008;Fleischman & Schuele, 2009;Bisman, 2011;Sánchez-Matamoros & Hidalgo, 2011;Bisman 2012). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting history is a masculinised sub-field. Carnegie et al (2003) found that only 12% of papers published in the three specialist accounting history journals to 2000 were contributed by women (predominantly from English speaking countries) and only 19% of individual members of the Academy of Accounting Historians were female. It might irritate some feminists to discover that much of the history of women in accounting has and continues to be written by men.…”
Section: A Review Of Progress Since 1992mentioning
confidence: 99%
“…One of these papers (Brinn and Jones, 2007) is a study of the editorial boards' composition at accounting journals using gender as a variable but without reference to language. Two studies that are published in AAAJ (Carnegie et al, 2003) and in Career Development International (2008) do not use language as a methodological tool but merely refer to the English language. Finally, the fourth paper (Walter et al, 2009) investigates language as a course compared with an accounting course.…”
Section: Resultsmentioning
confidence: 99%